Analisis Kebijakan Pengelolaan Dana Desa Untuk Percepatan Pembangunan Ekonomi Masyarakat Di Wilayah Perdesaan Kabupaten Tabalong - Norhalidah (Jurnal PubBis, 2026)
Rural economic development through Village Funds is a strategic priority for the government in realizing structural transformation in rural areas and reducing regional disparities. This study aims to analyze Village Fund management policies in accelerating community economic development in Tabalong Regency by identifying success determinants, implementation barriers, and formulating strategies for sustainable management optimization. A qualitative approach with a descriptive case study design was applied in five villages selected purposively based on the level of management success, accessibility, and variation in socio-economic characteristics. Data collection was conducted through in-depth interviews with seven informants from each selected village, participatory observation, and review of planning and accountability documents. Data analysis used an interactive model with triangulation of sources and methods to ensure the validity of the findings. The findings indicate that the implementation of the Village Fund policy has complied with existing regulations; however, its effectiveness in promoting rural economic development remains limited. Key constraints include limited human resource capacity, the dominance of physical infrastructure spending, suboptimal and non-inclusive community participation, and insufficient transparency and accountability. The results suggest that the success of Village Fund utilization depends on the synergy between village leadership, institutional capacity, good governance practices, and community involvement. Therefore, a policy reorientation toward a balanced allocation between physical development and productive economic empowerment, supported by sustainable institutional capacity strengthening, is essential to achieve inclusive and sustainable rural development.. The implications of this research provide recommendations for local governments to optimize the Village Fund, namely strengthening the capacity of village officials through continuous training, reorienting the allocation of the Village Fund to productive economic empowerment programs with a high multiplier effect, strengthening transparency and accountability through a simple reporting system and information technology, and implementing an intensive village assistance model with professional assistants and community participation through group empowerment forums